The Living Qur’an in the Domestic Sphere: The Transformation of the Function of Qur’anic Amulets in Minority Muslim Communities in Bali - Maziyyatul Hasanah; Rifqatul Husna (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This study examines the transformation of the function of Qur’anic amulets from a means of personal protection to a symbol of domestic spirituality in the Muslim minority community in Pemuteran, Bali. Using a phenomenological qualitative approach and a functional reception theory framework, this study traces how verses from the Qur’an—particularly verses on protection—are written on white cloth and placed on new buildings as a means of divine protection. Data was collected through field observations, documentation of amulet artifacts, and in-depth interviews with religious leaders, amulet writers, homeowners, and local communities. The results show that this practice is not merely a continuation of mystical traditions, but a dynamic manifestation of the Living Qur’an, in which the sacred text interacts with local cultural values, spatial symbolism, and communal identity. The shift in the function of amulets from individual protection to domestic protection reflects changes in spiritual, social, and cultural needs within Muslim communities living in predominantly Hindu environments. This practice also serves as a means of cultural negotiation that allows the community to maintain their Islamic identity while adapting to local Balinese traditions. This study contributes to the development of Living Qur’an studies by emphasizing how the holy text works in the domestic sphere and how Qur’anic symbols play a role in the negotiation of minority identity, spatial security, and cultural sustainability in a multicultural context.